Effect of crystallographic orientation on atom probe tomography geochemical data?. (October 2020) - Cappelli, Chiara; Pérez-Huerta, Alberto
Highlights: The study of the crystal orientation effect is of importance for the interpretation of APT data. APT bulk and isotopic mineral compositions are not affected by crystallographic orientation. 3D reconstructions are consistent for galena (100) and (001) planes and spinel (100) and (111) planes. 4. 2D density distribution maps do not vary significantly with the crystallographic orientation. Abstract: The recent application of atom probe tomography (APT) to minerals is becoming a powerful tool to unravel geological information from the nanoscale perspective. Yet, there are still unknown fundamental aspects of this microscopy technique for geological applications and the potential crystallographic orientation effect is a significant one. Here, the influence of the crystallographic orientation on the quality of atom probe tomography geochemical data is investigated for two minerals with the same crystal system and different morphology: spinel (isometric, hexoctahedral, octahedron morphology) and galena (isometric, hexoctahedral, cube morphology). Two separate crystals of barite (orthorhombic, dipyramidal, prism morphology) were also analyzed to test the reproducibility of APT data. Despite the general absence of expected stoichiometry, overall bulk and isotopic chemical composition are not affected by crystallographic orientation. 3D data reconstructions of the specimens showed similar spatial distribution of the ion species for each mineral and 2D density maps showed identical (barite, galena) or specular (spinel) patterns for each pair of planes analyzed. Our findings indicate a negligible effect of the crystallographic orientation in APT geochemical data for standard highly symmetric minerals but also suggest the possible influence of the crystallographic structure and composition on the mineral stoichiometry and elements spatial distribution density.